Stray-Light Suppression of the Internally Occulted Reflecting Solar Corona Imager - Zhang, Guang; Wang, Yunqi; He, Lingping; Wang, Xiaodong; Ren, Shuai; Xuan, Yubo; Liu, Fei; Chen, Bo (Frontiers in Physics, 2022)
In order to achieve a clear observation of the ultra-low brightness solar corona and provide a physical basis for forecasting space weather that seriously affects the human living environment, stray-light suppression level becomes the key factor affecting the development of the coronagraph. In this paper, a stray-light suppression method is adopted for Solar Corona Imager (SCI) which is a dual-waveband internally occulted reflecting coronagraph simultaneously and independently observing the inner corona in the HI Lyman-alpha (121.6±10nm) line and white-light (700.0±40nm) wavebands with a field-of-view (FOV) from 1.1 to 2.5R⊙(R⊙ stands for the mean solar radius).The scattered stray-light from the primary mirror, including the surface errors, cosmetic defects, particulate contamination are analyzed and suppressed ,and the corresponding scattering models are established for simulation based on the laboratory testing. The stray-light measurement results for SCI in the laboratory show that the stray-light level can be suppressed to the order of 10-8 B⊙ at 2.5R⊙(B⊙ is the mean brightness of the solar disk) in white-light(WL) band, which is consistent with the stray-light level obtained by simulation and verifies the modeling and simulation.